Carnevali, G., Pérez-García, E.A., Leopardi-Verde, C.L., Tapia-Muñoz, J.L., Cetzal-IX, W.R., Ramírez-Morillo, I.M. & Romero-González, G.A. (2018) The Encyclia ambigua complex (Laeliinae, Orchidaceae), a synopsis and notes on Encyclia virens and Epidendrum alatum. Phytotaxa 372 (1): 001–021. - Carnevali, Germán; Pérez-García, Eduardo A.; Leopardi-Verde, Carlos Luis; Tapia-Muñoz, José Luis; Cetzal-Ix, William R.; Ramírez-Morillo, Ivón M.; Romero-González, Gustavo A. (Phytotaxa, 2018)
N/A